Produktivitas Penyaluran Dana Zakat Terhadap Bina Modal Usaha Miskin Di Baznas Labuhanbatu - Yusrina Rsia Siregar; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
Distribution of zakat is the activity of distributing and using zakat for zakat mustahik. The distribution of zakat is carried out by the amil zakat agency formed by the government which is organized as an agency or institution. BAZNAS is a zakat management institution established by the government to collect and distribute zakat to zakat mustahik. Zakat can help mustahik develop their business. The purpose of this study was to determine the distribution of zakat with the aim of developing entrepreneurial capital. Labuhanbatu 2020-2021 with the aim of developing a productive company